Therapeutic effect of cucurbitine on dog taeniasis - Chen Zhi-kang; Pu Tian-chou; Li De-ying; Jiang Hong-an (Acta Pharmacologica Sinica, 2016)
Experimental therapy was carried out on 6 dogs. Cucurbitine hydrobromide or perchloride was given orally at a dose of 1-5 g. This amino acid expelled effectively Taenia hydatigena, Taenia pisiformis and Diphyllobothrium mansoni. Since cucurbitine merely paralysed the parasites, a carthartic dose of MgSO4 was routinely given after cucurbitine. No toxic symptoms but vomiting were observed after large doses.